2018
DOI: 10.1155/2018/1537170
|View full text |Cite
|
Sign up to set email alerts
|

Movement Velocity and Fluidity Improve after Armeo®Spring Rehabilitation in Children Affected by Acquired and Congenital Brain Diseases: An Observational Study

Abstract: Background Children with cerebral palsy (CP) and acquired brain injury (ABI) often exhibit upper limb impairment, with repercussions in their daily activities. Robotic rehabilitation may promote their functional recovery, but evidence of its effectiveness is often based on qualitative functional scales. The primary aim of the present work was to assess movement precision, velocity, and smoothness using numerical indices from the endpoint trajectory of Armeo®Spring. Secondly, an investigation of the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…However, significant improvements in terms of QUEST scale after the training with Armeo has been proven by El-Shamy [85], showing that robotic-assisted therapy is more effective than conventional therapy in promoting functional improvements of upper limbs, suggesting to combine conventional and robotic therapies for the achievement of better rehabilitation gains. In support of this thesis, another study [82] has demonstrated the improvement of functionality of the upper limbs after Armeo Spring training in children with CP and ABI. However, the researchers have noticed that the recovery was different between the two groups and that children with ABI improved essentially in the first period of training whereas children with CP in the second one.…”
Section: Robotic Protocols For Upper Limb Rehabilitationsupporting
confidence: 54%
See 2 more Smart Citations
“…However, significant improvements in terms of QUEST scale after the training with Armeo has been proven by El-Shamy [85], showing that robotic-assisted therapy is more effective than conventional therapy in promoting functional improvements of upper limbs, suggesting to combine conventional and robotic therapies for the achievement of better rehabilitation gains. In support of this thesis, another study [82] has demonstrated the improvement of functionality of the upper limbs after Armeo Spring training in children with CP and ABI. However, the researchers have noticed that the recovery was different between the two groups and that children with ABI improved essentially in the first period of training whereas children with CP in the second one.…”
Section: Robotic Protocols For Upper Limb Rehabilitationsupporting
confidence: 54%
“…This device records movement parameters such as resistance, strength, coordination and range of motion and is adjustable according to the patient's condition. We found 7 clinical studies involving this device [81][82][83][84][85][86][87]. It has been used primarily for clinical rehabilitation protocols for children with CP, demonstrating a better quality of upper limb movements due to improvements of QUEST and MAAULF scales at the end of the training [81][82][83].…”
Section: Robotic Protocols For Upper Limb Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Thus, the implementation of robotics primarily focuses on functional motor performance by providing intensive repetitive training, sensorimotor integration and cognitive engagement through goal-directed tasks to address the underlying symptoms and related problems due to client's neurological conditions. [34][35][36] From previous studies, the use of robotic devices has been found to improve kinematics, [37][38][39][40] range of motion, 41 42 muscle tone, 43 44 postural control 45 46 and functionality of upper 38 40 and lower extremities 47 48 among individuals with CP.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The Armeo Spring is a robotic device for hand rehabilitation which, with the help of exoskeletons with integrating springs, facilitates active movements of the upper limbs [26]. Software video games allow the patient to move his arms in different directions and perform more precise movements as well as squeeze [27].…”
Section: Robots For Upper Limb Rehabilitationmentioning
confidence: 99%